Secondary cases of meningococcal infection among close family and household contacts in England and Wales, 1984-7. - Cooke, R. P. (1989)
To determine the incidence of secondary meningococcal infection in close family and household contacts of index patients and to review the efficacy of chemoprophylaxis the records of 3256 cases occurring from 1984 through 1987 were examined. Seventeen secondary cases (0.5%) of infection were identified among these groups. The median interval between index and secondary cases was seven weeks. Fourteen secondary cases occurred more than one week after the disease was diagnosed in the index case. Three secondary cases had not received chemoprophylaxis and in another case the infecting strain had acquired resistance to rifampicin. Prophylaxis for the close contacts of 10 out of 11 of the remaining index patients failed to fulfil all the criteria of an optimal regimen. Even after optimal chemoprophylaxis the medical practitioner and the family should be aware of the increased and prolonged risk of secondary meningococcal infection among close contacts of patients with the disease.